Hemolytic anemia in dogs caused by the protozoan parasite Babesia canis and the impact of imidopyran and prednisolone - A. Nevidnyk-Pravda; G. Ushakova (Regulatory Mechanisms in Biosystems, 2025)
Babesiosis is a tick-borne disease caused by apicomplexan hemoprotozoan parasites that infect red blood cells. The condition can develop from small species of Babesia , such as B . gibsoni , B. conradae , and B. vulpes , as well as larger species like B. vogeli , B. canis , and B. rossi . The number of Babesia infections has been increasing globally in the world, and that is a significant problem for wild and domestic animals and for humans. Babesia is found throughout the world. Climate change, including rising temper a tures, altered precipitation patterns and prolonged warm spells , fosters tick reproduction and expand s their habitats into new regions. This shift significantly increases the risk of babesiosis being transmitted to areas where it was previously uncommon. Additionally, climate change may affect the seasonal behavior of ticks, extending their active periods and thereby elevating the risk of infection for both humans and animals. The overall health of animals can also be compromised by climate change, making them more su s ceptible to infections, which further facilitates the spread of various diseases. Recent reports highlight that Babesia canis is the most prevalent species found in Ukraine. However, information regarding the hematological and biochemical changes in dogs naturally infected with B. canis , particularly in Dnipro city, remains scarce. This study focuses on a retrospective analysis of clinical cases of Babesia infection in dogs. For this research, a complete biochemical profile was obtained and analyzed for 25 dogs diagnosed with babesiosis. Treatment administered within the first 24 hours for dogs with B. canis infection demonstrated improvement in several biochemical parameters in the blood, including superoxide dismutase (SOD), inorganic phosphorus, lactate dehydrogenase (LDH), and various protein fractions. This treatment effectively reduced renal and oxidative stress, as well as improved electrolyte, protein, and lipid metabolism. While some indicators, such as urea, creatinine, potassium, albumin, cholesterol, calcium, and sodium, did not show significant changes, the overall trends suggest that the therapy was effective in stabilizing the dogs' conditions and all e viating symptoms of hemolytic anemia. Ongoing monitoring and possible additional therapeutic interventions may be required to achieve a complete normalization of biochemical parameters.